A comparative study between the pioneer cohort of waterbirths and conventional vaginal deliveries in an obstetrician-led unit in Singapore - Karen M.X. Lim; Pearl S.Y. Tong; Yap-Seng Chong (Elsevier, 2016)
Objective: Waterbirth has been increasing in popularity in Asia (Lea W. Water babies. The Straits Times 17 February 2011. Available at http://www.nuh.com.sg/news/media-articles_1504.html). National University Hospital, Singapore, is the pioneer hospital offering waterbirths to women since 2006 in a unique setting of a consultant-led service and continuous foetal monitoring. To date, no studies have been done on the conduct of waterbirths in an Asia. This study aims to evaluate if water immersion during delivery is associated with increased rates of adverse maternal and foetal outcomes as compared with conventional vaginal deliveries. Materials and Methods: Clinical records of women who birthed underwater at National University Hospital between 2010 and 2013 were retrospectively reviewed. Outcomes of interest were estimated blood loss, third- or fourth degree tears, incidence of postpartum infections or haemorrhage, neonatal Apgars at 1 and 5 min, and neonatal complications requiring intensive care unit admission. Outcomes were compared against a matched control group of women who had conventional vaginal deliveries within ≤1 month. Results: Records of 118 women who birthed underwater were accrued. There was no significant difference in estimated blood loss and postpartum haemorrhage between groups, and there were no cases of maternal infection, third- or fourth-degree perineal tears, or adverse neonatal outcomes in either group. Women in the control group were more likely to have episiotomies (63.6% vs. 0.85%; p < 0.01). Three cases of retained placenta were reported in the waterbirth group (0.03%). Conclusion: Waterbirth at our centre does not appear to be associated with an increased incidence of adverse neonatal and maternal outcomes. The results of this study supported waterbirth as a birthing option to groups of low-risk women in an obstetrician-led setting with good midwifery support.